2021
DOI: 10.3389/fphar.2020.634963
|View full text |Cite
|
Sign up to set email alerts
|

Analgesics for Dental Implants: A Systematic Review

Abstract: Postsurgical pain is commonly associated with dental and oral surgery, and the use of analgesics has been investigated in the management of postoperative pain. This systematic review summarizes available evidence on analgesics used to manage dental implant surgery postoperative pain, to identify best therapeutic protocols and knowledge gap. A comprehensive search was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov, and the Cochrane Database of Systematic Reviews through May 2020. Only ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…The results showed that ibuprofen (600 mg) and dexketoprofen (25 mg) were superior to placebo for reducing pain. Further RCTs with an adequate sample size comparing standardized implant approaches are needed to inform best practices in this domain ( Melini et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that ibuprofen (600 mg) and dexketoprofen (25 mg) were superior to placebo for reducing pain. Further RCTs with an adequate sample size comparing standardized implant approaches are needed to inform best practices in this domain ( Melini et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nonaddictive analgesics, including NSAIDs and acetaminophen, are recommended as first-line agents in the management of pain following outpatient dental procedures (Hersh et al, 2020). Prior studies have demonstrated that prescription doses of NSAIDs are superior to placebo in reducing post-operative pain and swelling following implant placement surgery (Khouly et al, 2021;Mattos-Pereira et al, 2021;Melini et al, 2020). However, to our knowledge, this is the first study to compare the analgesic and anti-inflammatory effects of OTC doses of an NSAID and acetaminophen following implant placement surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous placebo-controlled studies support the use of non-steroidal anti-inflammatory drugs (NSAIDs) as first-line agents in managing pain following outpatient dental procedures due to their effectiveness and lack of addictive potential (Hersh et al, 2020;Moore & Hersh, 2013). Most of these studies have been performed in patients undergoing surgical extraction of bony impacted mandibular third molars, but similar results have been observed in studies of implant placement (Khouly et al, 2021;Mattos-Pereira et al, 2021;Melini et al, 2020). Pre-emptive administration of dexketoprofen 25 mg (Sanchez-Perez et al, 2018), ibuprofen 600 mg (Pereira et al, 2020), or piroxicam 40 mg (Bhutani et al, 2019), 15-60 minutes prior to surgery, resulted in less post-operative pain compared to placebo.…”
Section: Introductionmentioning
confidence: 92%
“…Non-addictive analgesics, including NSAIDs and acetaminophen, are recommended as first-line agents in the management of pain following outpatient dental procedures ( Hersh et al, 2020 ). Prior studies have demonstrated that prescription doses of NSAIDs are superior to placebo in reducing post-operative pain and swelling following implant placement surgery ( Melini et al, 2020 ; Khouly et al, 2021 ; Mattos-Pereira et al, 2021 ). However, to our knowledge, this is the first study to compare the analgesic and anti-inflammatory effects of OTC doses of an NSAID and acetaminophen following implant placement surgery.…”
Section: Discussionmentioning
confidence: 99%